Prevalence and factors associated with postpartum use of long-acting reversible contraception in Bukombe District, Geita Region, Tanzania: a community- based study - Kiondo Solomon Kiondo; Eusebious Maro; Sophia Kiwango; Julius Pius Alloyce; Benjamin C. Shayo; Michael Johnson Mahande (BMC, 2020)
Abstract Background Globally, approximately half of all pregnancies occur before 24 months after child birth. In Sub Saharan Africa the unmet need for family planning is highest among postpartum women. There is a dearth of information regarding factors associated with postpartum use of long acting reversible contraception (LARC) in Tanzania particularly in the Lake zone. This study aimed to determine the prevalence and factors associated with postpartum use of LARC (< 24 months) in Bukombe District, Geita Region in the Lake zone, in 2018. Methodology Community based analytical cross-sectional study was conducted between May and June 2018 among women with less than 24 months since delivery. Multistage sampling technique was used to recruit participants. Face to face interviews with 768 postpartum women was conducted using standardized questionnaire. Data were analyzed using Stata Version 13.0. Multivariable logistic regression model was used to determine factors associated with postpartum use of LARC. Results Prevalence of postpartum use of LARC was 10.4%. Urban residence (AOR = 2.94, 95% CI: 1.07-8.06), having formal employment (AOR = 4.81, 95% CI: 1.85-12.57) and receiving family planning counseling (AOR = 4.39, 95% CI: 1.89-10.20) were significantly associated with postpartum LARC use. Conclusion The postpartum use of LARC was low in the studied population with implants being the most commonly used method. Urban residency, formal employment and receiving family planning counseling were associated with postpartum LARC use. Improving prenatal and quality of family planning counseling is warranted to increase postpartum LARC utilization in Bukombe.